Effect of Different Packings on the Performance of Ice-slurry Wet Precooling Storage - Su Mingqiang; Wu Weidong; Ren Xueming; Li Xiang (Zhileng xuebao)
System performances with different packings (wire mesh corrugated, metal hole plate, ceramic corrugated, paper wet curtain, and plastic S-type) were examined to study the effect of packing on the performance of ice slurry wet pre-cooling systems. Key indicators are the temperature and humidity in the pre-cooling room, the pre-cooling process duration, the temperature variation coefficient, and the weight loss rate. The results showed that the final temperature of the circulating air in the precooling room could reach -1 ℃ with all types of packing, and the relative humidity of the air could be stabilized above 90%, meeting the precooling process requirements of pleurotuseryngii. When the ceramic corrugated and paper wet curtain packings were used in the pre-cooling room, the temperature variation coefficients were 0.26% and 0.28%, respectively, which are significantly less than the other packings (P<0.05), indicating that the pre-cooling of pleurotuseryngii was more uniform. When the wire mesh corrugated packing was used in the pre-cooling room, the pre-cooling process duration was significantly less than the other four packings (P<0.05), which was 70.2 min. When the wire mesh corrugated packing and metal hole plate were used in the precooling room, their weight losses were significantly lower than the other three packings (P<0.05), which were 2.65% and 2.85%, respectively, indicating that the weight loss of pleurotuseryngii was smaller than the others.